2019
DOI: 10.1021/acsaem.9b00365
|View full text |Cite
|
Sign up to set email alerts
|

Nonhalogenated Solvent-Processed Fullerene-Free Ambient Stable Organic Solar Cells: Impact of Molecular Weight of New π-Conjugated Donor Polymer on Efficiency

Abstract: Environmentally benign solvent-processed photoactive materials are urgently required to replace the current toxic solvent processing, especially for nonfullerene organic solar cells (NFOSCs). In this regard, we report an efficient new π-conjugated polymer (P1) for high performance NFOSCs. The careful choice of side chain, number-average molecular weight (M n) tuning (low, medium, and high M n, denoted as P12, P19, and P32), and dedicated device engineering of NFOSCs resulted an impressive device performance. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…The obtained Nyquist plot is shown in Figure 3c, fitted by the equivalent circuit. [ 29 ] The NFOSCs processed using P2:IT‐4F, P2:IT‐4F:BTP‐4F, and P2:IT‐4F:BTP‐4Cl exhibited bulk resistances of 1388.39, 937.16, and 728.86 Ω, respectively. The results are in good agreement with the J sc and FF values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained Nyquist plot is shown in Figure 3c, fitted by the equivalent circuit. [ 29 ] The NFOSCs processed using P2:IT‐4F, P2:IT‐4F:BTP‐4F, and P2:IT‐4F:BTP‐4Cl exhibited bulk resistances of 1388.39, 937.16, and 728.86 Ω, respectively. The results are in good agreement with the J sc and FF values.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26,27 ] Therefore, to satisfy the film morphology and device performance requirements using nonhalogenated solvents, we should analyze the compatibilities of π‐conjugated donor polymers and nonfullerene acceptors (NFAs) with nonhalogenated solvents. [ 28–30 ] However, few studies have addressed this aspect of NFOSCs. Hong et al reported a PCE > 15% when BTP‐4F was blended with modified alkyl chains blended with PBDB‐TF to produce a 100 nm active layer.…”
Section: Introductionmentioning
confidence: 99%
“…The new polymer donor Nap-SiBTz was synthesized by Stille polymerization (Scheme S2). , The detailed procedure used to synthesize Nap-SiBTz is described in Section and the Supporting Information. The structures of the new comonomer and Nap-SiBTz were confirmed by 1 H and 13 C NMR spectroscopies (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Organic solar cells (OSCs) technology is regarded as one of the most promising sustainable and green energy sources for their promise as environmentally friendly and easily printable devices. [ 1–6 ] In recent years, bulk‐heterojunction (BHJ) OSCs have made impressive strides in their power conversion efficiency (PCE) owing to novel material synthesis, morphology optimization and device engineering, [ 7–15 ] resulting in PCE of single‐junction devices over 18%. [ 16 ] However, most of the devices with cutting‐edge performance were fabricated by spin‐coating using highly toxic halogenated solvents under controlled conditions, which is not favorable to the large‐scale commercialization of OSCs.…”
Section: Figurementioning
confidence: 99%